SYSTEMATIC LITERATURE REVIEW (SLR) ANALISIS PERKEMBAGAN KURIKULUM PADA ERA TEKNOLOGI YANG BERBASIS ARTIFICIAL INTELLIGENCE (AI) - Abdul Rahman Nue; Nasto E Umpel; Nazril Ilham A.W.; Khairunnusa F. Mahmud; Arifyadi Eyato; Hafid Rahmandan; Sugeng Pramudibyo (Jambura Journal of Engineering Education, 2025)
The development of Artificial Intelligence (AI) is driving transformation in education, requiring adjustments to the curriculum. This study uses a Systematic Literature Review (SLR) to examine the development of Artificial Intelligence (AI)-based curricula at the global and Indonesian levels, focusing on competencies, teaching approaches, and implementation challenges. Data were obtained from reputable journals, conference proceedings, and academic reports between 2021 and 2025. The results show that Artificial Intelligence (AI) enhances personalized, adaptive, and interactive learning, as well as develops 21st-century skills such as critical thinking, problem solving, and digital literacy. Key challenges include limitations in teacher competency, infrastructure, access gaps, and ethical and privacy issues. Effective implementation of Artificial Intelligence (AI) requires teacher training, technology equity, and clear ethical guidelines. These findings confirm the potential of Artificial Intelligence (AI)-based curricula to create adaptive education that is relevant to future demands, while also serving as a guide for policymakers and educators.